Tahap literasi komputer komputer guru-guru sekolah menengah Zon A Bahagian Kuching/Samarahan - Abdul Wahed, Bin Rosli. (1998)
The purpose of this research was to investigate the computer literacy level of Kuching/Samarahan division (Zone A) secondary school teachers. It also attempted to identify the computer literacy level differences between teachers' education qualifications, academic majors, gender and school locations. The survey method was used which involved questionnaires to collect the data. The research instrument was designed based on modifications from several research instruments such as the Minnessota Computer Literacy and Awareness Test (1998), the Attitude Scale Rating (1998) and the Computer Self-Efficacy Scale (1998). The questionnaires were used to investigate three computer literacy domains such as attitude towards computer use, computer knowledge and computer skill.